HUBUNGAN WAKTU REAKSI DENGAN KELINCAHAN TENDANGAN SAMPING PESILAT PERGURUAN SENI BELADIRI KEMBANG KAMANGO - Wan Abdul Rahim; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The Problem of the reaserch was less ability side kick from fireworks art self defense kembang kamango. This study aims to prove whether the correlation of reaction time with the agility side kick From Fighter Community Art Self Defense Kembang Kamango, so that during the attack side kick fighter can about his opponent. Forms of this research is a correlation study, the sample in this study fighter from Community Art Self Defense Kembang Kamango numbered 20 people. The first analysis of calculation of the correlation of variable X and variable Y, study, the sample in this study fighter from Community Art Self Defense Kembang Kamango numbered 20 people. The first analysis of calculation of the correlation of variable X and variable Y, where rtable at significant level α (0.05) = 0.190 means rresult (0.8347) > rtable (0.190), meaning that the hypothesis is accepted and there is a very strong correlation between time reaction is toagility side kick next to the from fighter Community Art Self Defense Kembang Kamango. Then it can be concluded that the correlation between the variable X with variable Y or the correlation between the reaction time and agility side kick is very powerful. Thus the agility side kick Fighter form Community Art Self Defense Kembang Kamango.Keywords: Reaction Time, Agility Side Kick